A low-temperature sealing method for metal-supported oxide fuel cell applications: Ni–Sn transient liquid phase bonding. (May 2021) - Cao, Jian; Zheng, Mushi; Wang, Zhiquan; Si, Xiaoqing; Li, Chun; Wang, Xiaoyang; He, Zongjing; Qi, Junlei
Abstract: A low-temperature sealing approach, transient liquid phase bonding with Ni–Sn system, was employed to seal metal-supported solid oxide fuel cell (MS-SOFC) components in this study. The Ni layer was prefabricated on the ferritic stainless steels by electroplating firstly, and then were vacuum annealed to enhance the bonding between the Ni coating and the steel substrate. Afterward, the Ni coated steels were transient liquid phase bonded using a thin interlayer of pure Sn. Effects of bonding temperature (250–400 °C) and holding time (10–60 min) on the interface of joints were investigated. The interfacial microstructure of joints was observed by the scanning electron microscope and the transmission electron microscope. A joint with full intermetallic compounds (IMCs) of Ni3 Sn4 and Ni3 Sn2 were formed at 400 °C/60 min. These Ni–Sn IMCs were all stable up to 794.5 °C, ensuring that the joint with full IMCs microstructure can be performed at the operating temperature of ∼600 °C for MS-SOFC. Furthermore, the residual Ni coating can also be served as a protective layer for the stack. Highlights: A low-temperature TLP bonding method is employed to seal MS-SOFC components. Vacuum annealing is applied to enhance the bonding between Ni coating and steel substrate. The desired joint, consisting of full IMCs, is successfully achieved at 400 °C. Microstructure analysis shows all the phases in the joint are stable at ∼600 °C.